A Comparative Study on Quality of Fermented Shrimp Paste (Terasi) of Pelagic Shrimp from Different Locations in Indonesia - Henny Helmi; Dea Indriani Astuti; Rudi Dungani; Pingkan Aditiawati (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2022)
This study aims to determine and compare the quality of Indonesian fermented shrimp paste (terasi) produced from pelagic marine shrimp using a traditional preservation method (fermentation, drying, and salting). The quality of fermented shrimp pastes from different locations in Indonesia (Sungsang district, South Sumatra; Toboali district, Bangka Belitung Islands; Indramayu, West Java; Tegal, Central Java; Madura, East Java; Bontang, East Kalimantan and Sumbawa, West Nusa Tenggara) was determined by evaluating its parameters (i.e., physicochemical, microbiological, and sensory). This study found that the fermented shrimp pastes quality differed among locations due to the processing method used (i.e., fermentation, salting, and drying), not the raw material characteristics, as indicated by the Principal Component Analysis (PCA). The first group (Sumatra and Sumbawa terasi samples) with a similar added salt percentage and length of fermentation resulted in similar pH, salinity, salty taste, and more preferred taste. The second group (Java and Kalimantan terasi samples) with similar lengths of first and second sun-drying resulted in similar chemical compositions such as higher protein content, lipid content, moisture content, total amino acid, and bitter taste. Terasi from Toboali prepared using Acetes japonicus with 48 h of fermentation produced the most nutritious and preferred taste by the panelists.